On the Choice of Royalty Rule to Cover Fixed Costs in Input Joint Ventures - Kenneth Fjell; Oystein Foros; Hans Jarle Kind (Center for Economic Studies and ifo Institute (CESifo), 2013)
In a model where two competing downstream firms establish an input joint venture (JV), we analyze how different royalty rules for covering fixed costs affect channel profits. Under running royalties (regardless of whether based on predicted or actual output), the downstream firms' perceived marginal costs are above the true marginal costs since fixed costs are incorporated. We find that tougher competition between the JV partners may actually increase channel profit under such a scheme. We also show that running royalties based on predicted output are outperformed by royalties based on actual output, but that lump-sum financing of the JV is preferable if the competitive pressure is weak.
Keywords: L10; 330; input joint ventures; competition; royalty rules